Evaluation of a quantitative scoring of enthesitis in ankylosing spondylitis - Kaya, Arzu; Ozgocmen, Salih; Kamanli, Ayhan; Aydogan, Rabia; Yildirim, Arafe; Ardicoglu, Ozge (Lippincott Williams & Wilkins, 2007)
Background: Enthesitis is inflammation at the insertion of ligaments, tendons, joint capsule, or fascia to bone, and a well-known characteristic feature of ankylosing spondylitis (AS) and related spondyloarthropathies. The clinical evaluation of enthesitis is an important outcome measure and is scored by applying pressure on entheses to elicit tenderness at these sites. Objective: This study assessed the validity of an enthesitis index calculated by algometric pressure pain threshold scoring in comparison with digital palpation scoring and intra- and interexaminer reliability of 2 grading methods of the Maastricht Ankylosing Spondylitis Enthesitis Score (MASES). Patients and Methods: Five hundred forty six entheses were examined in AS patients. Examination was performed on enthesopathy regions proposed by MASES. All of these entheses were examined by firm palpation with the thumb, and tenderness was graded on a 4-point scale. The summed tenderness scores were expressed as total palpation pain score (t-PS). After this procedure, the same entheses were rescored by using a mechanical algometer, and the sum was expressed as total pressure pain threshold (t-PPT). Fifteen indicators of functional, disease-activity, and anthropometric measures were used including global assessment of disease activity on a 0 to 100 nun visual analogue scale (global), Bath Ankylosing Spondylitis Disease Activity Index, Health Assessment Questionnaire-SpA, Dougados Functional and Articular Index, Bath Ankylosing Spondylitis Functional Index, ESR, CRP, occiput-to-wall distance, finger-to-floor distance, finger-to-fibula distance, chest expansion, and duration of morning stiffness in minutes. Results: There was a significant correlation between clinical variables and t-PS and t-PPT, which was better for t-PS. Intraexaminer reliability was moderate to excellent for digital palpation scoring (intraclass correlation coefficients 0.55-0.96) and algometric scoring (0.54-0.96). Interexaminer reliability was fair to excellent for digital palpation scoring (0.43-0.84) and moderate to excellent (0.52-0.88) for algometric scoring. Conclusion: Our results indicate that algometric evaluation of entheses does not add extra information to clinical relevance of MASES, and grading with digital palpation is a more convenient, practical, and reliable examination method for the assessment of enthesitis.
Keywords: ankylosing spondylitis; enthesitis; clinical relevance; Maastricht Ankylosing Spondylitis Enthesitis Score (MASES); algometric pressure pain threshold